A pressuposição como mecanismo implícito na interpretação dos ditados populares - LARANGEIRA, Laurena Marques (2019)
This article tries to understand how the process of interpretation of popular sayings happens, based on the theory of the Ducrot (1987) presupposition, with the objective of analyzing these expressions, highlighting their respective assumptions. Throughout the interview with 5 (five) elderly people, such a mechanism was detected, questioning the informants about how they contextualize these expressions, from the information declared to confirm the common sense of each said, that resulted in the ratification of their assumptions. In this interpretative process, the presuppositions stand out in the foreground, and in the background the knowledge previously absorbed by the speakers and the way in which they make use of these expressions. With this, one arrives at the perspective that the dictates are used with indirect effect and the presuppositions detected in the sayings reflect not only the intention, but also the ideology from which the utterance was constructed. Then, the assumption becomes considered as a mechanism that allows to interpret what is present between the lines of dictations.